The Uncanny in the Themes of Evil, Transgression and the Double in Nathaniel Hawthorne's "Rappaccini's Daughter" - Barboza Núñez, Esteban (2006)
El propósito de este artículo consiste en explorar los mecanismos y representaciones de lo siniestro en "La hija de Rappacci" de Nathaniel Hawthome como expresión del mal dentro de los límites del género gótico del siglo XIX; como expresión del tema del doble en tres personajes humanos y en uno no humano que aparecen en el cuento; y como expresión de trasgresión en el personaje principal, Giovanni Guasconte. El concepto de lo siniestro que se usará será el de la teoría psicoanalítica, siguiendo especialmente los aportes de Sigmund Freud y Jacques Lacan. The purpose of this artide is to explore the mechanisms and representations of the uncanny in Nathaniel Hawthome's "Rappaccini's Daughter" as an expression of evil within nineteenth century Gothic boundaries; as an expression of the theme of the double in three human characters and in one non-human component of Rappaccini's garden; and as an expression of transgression in Giovanni Guasconte, the main character. The concept of the uncanny to be used will be that of psychoanalytic theory, especially reliant on the contributions on the topic by Sigmund Freud and Jacques Lacan.